Cyberbullying : bullying in the digital age - Kowalski, Robin M.; Limber, Sue.; Agatston, Patricia W. (Malden, MA : Wiley-Blackwell, 2012)
'Psychologists explore the reality of cyberbulliesMillions of children are affected by bullies each year. Advances in social media, email, instant messaging, and cell phones, however, have moved bullying from a schoolyard fear to a constant threat. The second edition of Cyberbullying offers the most current information on this constantly-evolving issue and outlines the unique concerns and challenges it raises for children, parents, and educators. Authored by psychologists who are internationally recognized as experts in this field, the text uses the latest research in this area to provide an updated, reliable text ideal for parents and educators concerned about the cyberbullying phenomenon'--
'Bullying affects millions of children throughout the world each year. Recent advances in technology have led to greater prevalence of cyberbullying using e-mail, instant messages, social networking sites, and other digital messaging systems. The second edition of Cyberbullying provides the most current information on the nature and prevalence of this quickly-evolving issue that causes unique challenges and concerns for children, parents, and educators. Examining the latest research and methods for studying this issue, the authors have utilized vital studies involving over 3500 middle-school students, online research projects on cyberbullying on blogs, and data from focus groups of victims, perpetrators, and their parents. This edition includes updated and expanded empirical data; coverage of the newest digital venues where cyberbullying is appearing, including social networking sites; and a look at occurrences of cyberbullying among adults and among children with disabilities. The book also covers sexting and some of the legal issues surrounding it. The authors--internationally known experts in the field--provide practical tips for parents and educators on how to prevent cyberbullying through family and classroom discussions about proper online behavior. They also offer suggestions for successful intervention techniques in cyberbullying episodes that stem from their own work, research, and experiences'--
Includes bibliographical references and index.
Keywords: Cyberbullying; Bullying